On Saint Venant - Kirchhoff imperfect interfaces. (March 2017) - Rizzoni, R.; Dumont, S.; Lebon, F.
Abstract: Using matched asymptotic expansions with fractional exponents, we obtain original transmission conditions describing the limit behavior for soft, hard and rigid thin interphases obeying the Saint Venant-Kirchhoff material model. The novel transmission conditions, generalizing the classical linear imperfect interface model, are discussed and compared with existing models proposed in the literature for thin films undergoing finite strain. As an example of implementation of the proposed interface laws, the uniaxial tension and compression responses of butt joints with soft and hard interphases are given in closed form. Abstract : Highlights: Contact laws replacing thin interphases made of a non linear material are proposed. The Saint Venant-Kirchhoff material model is assumed. Soft, hard and rigid thin interphases are studied. Matched asymptotic expansions with fractional exponents are used. A butt joint is analyzed.